PEMIKIRAN SYEKH MUHAMMAD ARSYAD AL-BANJARI: ANALISIS KITAB TUHFATU AR-RAGHIBIN DAN RELEVANSINYA TERHADAP PENDIDIKAN KONTEMPORER - Zaid Muhammad Abduh; Asep Rahmatullah (As-Sulthan Journal of Education, 2026)
Contemporary Islamic education tends to emphasize cognitive and instrumental aspects, leading to the weakening of faith, adab, and character formation. This article analyzes the thought of Shaykh Muhammad Arsyad al-Banjari through the study of Tuhfatu ar-Raghibin and examines its relevance to contemporary education. This study employs library research with content analysis techniques. The findings indicate that Shaykh Muhammad Arsyad al-Banjari views faith as an integrated unity of belief, speech, and action, serving as the foundation of character education. His thought is integrative and normative, emphasizing the importance of a clear value paradigm and scholarly authority in Islamic education. These findings remain relevant for strengthening character education and integrating faith, knowledge, and adab in contemporary educational contexts.